Notes for a Typology of the Literary Semiosphere in Roberto Bolaño - Soto Bogantes, Carlos (2016)
From the perspective of the semiotics of culture (Lotman), a textual approach is proposed for the narrative of Roberto Bolaño. Reference is made to semiosphere and the text within the text. The analysis focuses on significant elements, such as memory. The aim is to systematize the model of literary semiosphere in the works of the Chilean writer.